(untitled) (New York, 2005)
The editors have succeeded in bringing together an excellent mix of leading scholars and practitioners. No book on the WTO has had this wide a scope before or covered the legal framework, economic and political issues, current and would-be countries and a outlook to the future
Keywords: Tổ chức thương mại thế giới,World Trade Organization